Sister Kinetochore Recapture in Fission Yeast Occurs by Two Distinct Mechanisms, Both Requiring Dam1 and Klp2 - Gachet, Yannick (The American Society for Cell Biology, 2008)
In eukaryotic cells, proper formation of the spindle is necessary for successful cell division. We have studied chromosome recapture in the fission yeast Schizosaccharomyces pombe. We show by live cell analysis that lost kinetochores interact laterally with intranuclear microtubules (INMs) and that both microtubule depolymerization (end-on pulling) and minus-end–directed movement (microtubule sliding) contribute to chromosome retrieval to the spindle pole body (SPB). We find that the minus-end–directed motor Klp2 colocalizes with the kinetochore during its transport to the SPB and contributes to the effectiveness of retrieval by affecting both end-on pulling and lateral sliding. Furthermore, we provide in vivo evidence that Dam1, a component of the DASH complex, also colocalizes with the kinetochore during its transport and is essential for its retrieval by either of these mechanisms. Finally, we find that the position of the unattached kinetochore correlates with the size and orientation of the INMs, suggesting that chromosome recapture may not be a random process.